MENINGKATKAN HASIL BELAJAR BIOLOGI PADA KONSEP JARINGAN TUMBUHAN DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) - Misrita Jalal, S.Pd (LP3M | STKIP YPM Bangko, 2022)
This research was conducted with the aim of improving the biology learning outcomes of class XI IPS 1 students in the 2018/2019 academic year at SMA Negeri 1 Merangin through the STAD type cooperative learning model. This research is a Classroom Action Research (CAR). The subjects of this study were students of class XI IPS 1, totaling 28 students. The research was conducted in two cycles and each cycle consisted of two meetings. Data collection techniques in this study used observation sheets, diary journals, and tests. The data obtained were analyzed by means of reduction, data exposure and conclusions. Descriptive data analysis was also carried out for observational data and daily journal entries. The research was conducted in stages including: planning learning, determining basic competencies, developing learning scenarios according to the 2013 KTSP curriculum, preparing learning resources. At the stage of implementing the action, namely by carrying out actions according to the learning scenario, which includes initial activities, core activities, and closing. At the reflection stage, it is carried out after the learning process in class in each cycle. From the results of observations and journal entries, the study showed that there was an increase in student learning outcomes as indicated by the average value of the results of the pretest and posttest implementation of each cycle. The average value of the pretest in cycle 1 was 53.93 and the average value of the posttest of students was 72.75. In cycle 2 the average value of the pretest was 60.29 and the average value of the posttest of students increased to 82.29. This means that it can be concluded that the application of the STAD type cooperative learning model can improve student biology learning outcomes on plant tissue material in class XI IPS 1 SMA Negeri 1 Merangin in the 2018/2019 school year.